Sengketa Merek Dagang Ayam Geprek Bensu Versus I Am Geprek Bensu - Amelia Puspita Sari (Jurnal Hukum Lex Generalis, 2025)
The trademark dispute between Ayam Geprek Bensu and I Am Geprek Bensu illustrates the complexities of trademark protection in Indonesia, especially under the first to file principle in Law No. 20 of 2016. This principle prioritizes formal registration over prior use, impacting many UMKM who lose brand rights to earlier registrants. The case highlights legal protection gaps and low awareness among UMKM about trademark registration. This research uses a normative juridical method with case and statutory approaches to analyze legal reasoning, the impact of first to file, and how Indonesia’s trademark system affects UMKM’s ability to protect their business identity.